Enamel and dentin shear bond strength of a self-adhering flowable composite compared to a conventional flowable composite - Austria, Ena Paula Q.
Advances in adhesive dentistry have led to the development of new restorative materials that offer a simpler application technique and less procedural errors. These are two factors that could affect bond strengths to tooth structure. A recently introduced material is the self-adhering flowable composite which the manufacturer claims to have comparable bond strengths with conventional flowable composite. The aim of this study is to compare shear bond strength of a self-adhering flowable composite to a conventional flowable composite/adhesive system on the enamel and dentin surfaces of human permanent teeth. METHODS: Forty enamel and forty dentin flat surfaces were randomly distributed to 8 groups (n=10), and served as the bonding substrate for the self-adhering flowable composite and the conventional flowable composite used with and without an adhesive system. A hollow plastic tube with a height of 5mm and inner diameter of 3mm was used to define the bonding area. SBS was measured using the Shimadzu Universal Testing Machine with a cross-head speed of 0.5mm/min. The data collected were analyzed using two separate non-parametric Kruskal-Wallis tests and post hoc test. RESULTS: The type of treatment protocol and restorative material used had significant effect on the enamel and dentin SBS. There were no significant differences on the SBS of E1 and E3 (p=0.895), but statistically significant differences were noted on the SBS of D1 and D3 (p=0.000). Groups E2 and D2 exhibited the highest SBS compared to other treatment groups, while groups E4 and D4 produced the lowest SBS. CONCLUSION: The self-adhering flowable composite have (1) comparable enamel SBS with the conventional flowable composite, but exhibited lower dentin SBS, and (2) bond strengths can be significantly improved when used with a separate adhesive system.